Shadow banking and the design of macroprudential policy in a monetary union - Philipp Kirchner; Benjamin Schwanebeck (Philipps-University Marburg, School of Business and Economics, 2020)
This paper studies the interaction of international shadow banking with monetary and macroprudential policy in a two-country currency union DSGE model. We find evidence that cross-country financial integration through the shadow banking system is a source of financial contagion in response to idiosyncratic real and financial shocks due to harmonization of financial spheres. The resulting high degree of business cycle synchronization across countries, especially for financial variables, makes union-wide policy tools more effective. Nevertheless, optimal monetary policy at the union-level is too blunt an instrument to adequately stabilize business cycle downturns and needs to be accompanied by macroprudential regulation. Our welfare analysis reveals that the gains from the availability of country-specific prudential tools vanish with the degree of financial integration as union-wide macroprudential regulation is able to effectively reduce losses among the union members.
Keywords: E32; E44; E58; F45; 330; financial frictions; shadow banking; currency union; financial integration; macroprudential policy